Effect of hydroxyapatite particle morphology on as-spun poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/hydroxyapatite composite fibers - Sabrina Kopf; Dan Åkesson; Minna Hakkarainen; Mikael Skrifvars (Results in Materials, 2023)
Hydroxyapatite (HA) has shown very promising results in hard tissue engineering because of its similarity to bone and hence the capability to promote osteogenic differentiation. While the bioactivity of HA is uncontested, there are still uncertainties about the most suitable hydroxyapatite particle shapes and sizes for textile scaffolds. This study investigates the influence of the shape and size of HA particles on as spun fibers of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and HA, their mechanical and thermal properties as well as their influence on the fiber degradation in simulated blood matrix and their capability to mineralize in simulated body fluid. The key findings were that the different HA particles’ size does not affect the melting temperature and still maintains a thermal stability suitable for fiber production. Tensile testing revealed decreased mechanical properties for PHBV/HA as spun fibers, independently of the particle morphology. However, HA particles with 30 nm in width and 100 nm in length at 1 wt% HA loading achieved the highest tenacity and elongation at break amongst all composite fibers with HA. Besides, the Ca/P ratio of their mineralization in simulated body fluid is the closest to the one of mineralized human bone, indicating the most promising bioactivity results of all HA particles studied.